Abū Al-Ḥasan Al-Masʻūdī on pre-Islamic Arab religions and belief - Alias, Majdan; Abdul Jalil, Mohd. Noh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims to shed light on one aspect of the contributions of an early Muslim historian of religion, Abū al-Ḥasan al-Masʻūdī. It focuses on al-Masʻūdī’s work on pre-Islamic Arab religions and beliefs. The study is based on textual analysis of al-Masʻūdī’s treatment of the issue in his Murūj (The Meadows), and comparisons are made with al-Masʻūdī’s treatments of the non-Arab religions.